Imagine Paul: Apostle of God - Greene, G. Roger (Pickwick Publications, 2024)
"Can the real Paul the apostle live again in a postmodern, technological age? Paul's ministry stood at the very headwaters of the Christian gospel surrounding Jesus of Nazareth. His letters are the earliest documents contained in the New Testament. The current work calls upon the reader to actively engage Paul in his context, rather than to affirm the assumed theological Paul of later Christian orthodoxy. The reader is thus invited to walk with a more real Paul as he may be imagined from the sources we have, to think Paul's thoughts with him through his letters, and to more fully experience the gospel of God that Paul knew and proclaimed. Paul was a "man in Christ" directly called by God to announce the gospel of God to both Jew and gentile in the midst of a world ruled by Rome. He did so through two major campaigns, rather than "three missionary journeys." He wrote pastoral letters to real first-century churches. The real Paul did not write theology, but he rather proclaimed a gospel to a world in search of a soul." --Page [4] of cover